AN ANALYTICAL STUDY ON WORK LIFE BALANCE IN EMPLOYEE RETENTION WITH SPECIAL REFERENCE TO IT AND BPO SECTORS - Singh, Dr. Rajendra; Dubey, Ms. Khushbu (IJRDO - Journal of Applied Management Science, 2016)
In modern times, employee’s retention has become one of the leading challenges fororganization, especially for service sector. The issue isn't simply losing a key member of yourteam; there is also the hassle-and cost-of replacement. It is obvious that employee’s retentionis one of the most pressing issues that Human Resource Professionals face today. Thisproblem becomes critical when the employee is unable to maintain the balance between worklife and family relationship. In that situation mostly employees leave the organization as theyfeel that in this organization their emotions, feelings and passions are not given recognitionand their employers are not going to cooperate in any way. Hence, in this study, the effect ofwork life balance has been examined in lieu of the employee retention. Correlation andregression were applied to conclude the findings of this research study.